2006
DOI: 10.1039/b605882e
|View full text |Cite
|
Sign up to set email alerts
|

A mild and convenient synthesis of N-carbobenzyloxy ketimines

Abstract: N-Carbobenzyloxy (Cbz) ketimines were prepared conveniently from N-Cbz amines by oxidation with N-tert-butylbenzenesulfinimidoyl chloride.N-Carboalkoxy aldimines are often used as nitrogen-containing electrophiles for carbon-carbon bond forming reactions, especially for highly enantioselective reactions such as the Mannich type reaction 1 and the aza-Henry reaction. 2,3 N-Carboalkoxy amines having a chiral tertiary carbon center are stereoselectively constructed by these reactions. Given this, N-carboalkoxy ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Condensation of amides or carbamates with carbonyl derivatives does not represent a viable procedure for the preparation of N ‐acylimines because of the unfavorable equilibrium for the imine formation. Thus, apart from some particular procedures involving acylation of N ‐trimethylsilylimines, condensation with iminophosphoranes, or oxidation of N ‐carbamoylamines, the general method for the preparation of compounds 1 involves a three component coupling of the amido derivative with an aldehyde and an heteronucleophile capable of generating stable compounds of type 3 – 5 (Scheme ). The obtained compounds are usually stable derivatives, easy to purify and store, which upon treatment with a suitable base suffer elimination of the heteronucleophilic moiety R 3 XH generating the N ‐acylimine 6 .…”
Section: Preparation Of N‐acyliminesmentioning
confidence: 99%
“…Condensation of amides or carbamates with carbonyl derivatives does not represent a viable procedure for the preparation of N ‐acylimines because of the unfavorable equilibrium for the imine formation. Thus, apart from some particular procedures involving acylation of N ‐trimethylsilylimines, condensation with iminophosphoranes, or oxidation of N ‐carbamoylamines, the general method for the preparation of compounds 1 involves a three component coupling of the amido derivative with an aldehyde and an heteronucleophile capable of generating stable compounds of type 3 – 5 (Scheme ). The obtained compounds are usually stable derivatives, easy to purify and store, which upon treatment with a suitable base suffer elimination of the heteronucleophilic moiety R 3 XH generating the N ‐acylimine 6 .…”
Section: Preparation Of N‐acyliminesmentioning
confidence: 99%
“…We found that the oxidation of α-alkynyl and alkenyl-substituted N -Boc-propargylic amines 4 with manganese dioxide afforded unprecedented N -Boc-protected dialkynyl ketimines and alkenyl alkynyl ketimines 6 in good yields (Table ). , While N -Boc-dialkynyl ketimines were obtained as a 1:1 mixture of E - and Z -isomers (entries 1–3 and 5), Z -ketimine 6d was formed exclusively in the case of an N -Boc-alkenyl alkynyl ketimine (entry 4), and a cis / trans isomerization of the styryl group was not observed (entry 4)…”
mentioning
confidence: 99%
“…18,19 N-Benzyloxycarbonyl ketimines 11 are also prepared by oxidation of lithiated N-Cbz amines 9 using sulfinylimidoyl chloride 10 at low temperature (Scheme 2). 20 This procedure works on a range of a-substituted amines, but in some of the reported examples, when R 1 = Me or with N-Cbz cycloalkylamines, a consistent amount of the parent enecarbamate 12 is observed as co-product. In order to avoid this tautomerization, the reaction mixture is treated at -78°C with methanol that traps the ketimine as the corresponding N,O-ketal, as demonstrated here for the reaction of cyclohexanamine derivative 13 converted into ketal 15 via imine 14.…”
Section: Preparation Of N-acyliminesmentioning
confidence: 95%